Physical preparation for canoe slalom - Jayes, J.
- Anaerobic Lactlc Tralnlng - ATP-CP Alactic - The Weekly Programme - Out of Season - Peaking - Recovery - Technique (within this structure) - Monitoring and Testing - Starting the Slalom Performance Test